2021
DOI: 10.30998/g.v1i1.696
|View full text |Cite
|
Sign up to set email alerts
|

Komunikasi Efektif Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19

Abstract: Sejatinya manusia membutuhkan Interaksi dengan sesame untuk saling memberi informasi atau yang lebih dikenal dengan komunikasi. Indonesia dan Negara lain sedang dilanda pandemi Covid -19 yang menyebabkan terjadinya lockdown, Interaksi sangat dibatasi bahkan beberapa tempat umum dilarang melakukan kegiatan termasuk Universitas. Selama masa pandemi universitas menerapkan pembelajaran secara daring dimana metode ini adalah hal baru bagi Indonesia. Dosen sebagai garda terdepan dalam proses pembelajaran harus mempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…Another aspect of the quality of implementing blended learning, evaluated through teacherstudent communication during learning activities, showed that communication was interactive and of reasonable quality, both in online and face-to-face learning. Teachers employed three forms of communication in blended learning, which were also found in Iswari's (2021) study: (1) informative communication, where teachers provide information and learning material to students online and inperson; (2) persuasive communication, which aims to change behaviors or habits, such as motivating students to stay active during the learning process; and (3) instructive communication, used for assignment collection and assessment.…”
Section: Evaluation Of Blended Learning In Biology Subject At State S...mentioning
confidence: 85%
See 1 more Smart Citation
“…Another aspect of the quality of implementing blended learning, evaluated through teacherstudent communication during learning activities, showed that communication was interactive and of reasonable quality, both in online and face-to-face learning. Teachers employed three forms of communication in blended learning, which were also found in Iswari's (2021) study: (1) informative communication, where teachers provide information and learning material to students online and inperson; (2) persuasive communication, which aims to change behaviors or habits, such as motivating students to stay active during the learning process; and (3) instructive communication, used for assignment collection and assessment.…”
Section: Evaluation Of Blended Learning In Biology Subject At State S...mentioning
confidence: 85%
“…1 of 2020 regarding the prevention of the spread of Corona Virus Disease in schools and universities. According to Iswari (2021), distance learning with the support of electronic learning technology (elearning) has truly been fully implemented due to the pandemic situation. In line with this, the learning activities of biology, especially in high schools, must be able to adapt to the situation that occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Kita harus terus bergerak walaupun pergerakan kita terbatasa bahkan bersyarat. Banyak tantangan yang kita hadapi bersama saat pandemic ini diantaranya adalah bagaimana kegiatan belajar mengajar berjalan tanpa harus tatap muka antar dosen dengan taruna, terutama mata kuliah praktek yang menghasilkan output taruna 'harus mengenal dan harus bisa' (Iswari, 2021). Tatap muka tetap dijalankan namun ada kita harus mengikuti protocol kesehatan yang telah ditetapkan oleh Pemerintah Pusat, Pemerintah Daerah maupun Satuan Gugus Covid setempat.…”
Section: Pendahuluanunclassified
“…Data kualitatif dalam penelitian ini adalah data yang tidak berupa angka-angka, melainkan berupa penjelasan atau keterangan yang mendukung penelitian. Ada empat macam teknik komunikasi, yaitu Komunikasi Informatif, Komunikasi Persuasif, Komunikasi Instruktif/Koersif dan Hubungan manusiawi (Iswari, 2021). Penelitian komunikasi adalah untuk memahami realitas sosial, dan karenanya keberadaan metode membantu kita memahami fenomena-fenomena dan permasalahan komunikasi yang actual (Haryono, 2020).…”
Section: Metode Penelitianunclassified